An Investigation of Self-Esteem and Athletes’ Performance Association: A Gender and Format of Sports-based Study of College Level - Ambreen, Sidra; Hussain, Farooq; Shah, Muhammad (Annals of Human and Social Sciences, 2025)
The aim of current research was to investigate the relationship between Self-Esteem and sports Performance of male and female players. Main objectives of the study were as:To determine the comparison between male and female athletes’ self-esteem and sports performance and to analyze the significant difference about self-esteem level of the players of different localities. Study Population comprised of the male and female players of Government associate and commerce Colleges. Two hypotheses were formulated for testing. As population is very limited and easily approachable, so census method was applied for sample selection of the study. Self-esteem standardized scale by by Naimat, (2020) was adopted and used for data collection. Moreover, the researcher used quantitative research method for data collection. Descriptive statistics (Mean and standard deviation) and inferential statistics (two-way ANOV) were used to analyze and tabulate the collected information. It was found that that there is no significant correlation between male and female athletes’ self-esteem and volleyball & badminton performance. Moreover, there was no significant difference about self-esteem of the players in terms of locality. However, it is crucial to create an environment that is encouraging and supportive of athletes’ self-esteem because it might have wider ramifications for psychological and general health. LPEs should concentrate on the unique traits and requirements of each player rather than drawing generalizations based on their location.